Sistem Pendukung Keputusan Pemilihan Tempat Wisata Terbaik di Kota Surakarta Menggunakan Metode SAW - Dwi Wahyuningtyas; Dhika Neissa Asanti; Septi Dwi Supriati; Bunga Amalia Putri (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This article discusses the development of a decision support system (DSS) for selecting the best tourist attractions in Surakarta City using the Simple Additive Weighting (SAW) method. The background of the research is the importance of choosing the right tourist attractions to enhance visitor satisfaction and support regional development. The SAW method was chosen for its ability to provide structured assessments based on multiple criteria. This study uses an Agile approach in system development, involving planning, analysis, design, implementation, and testing stages. The results show that the developed decision support system can effectively manage the criteria and alternatives for tourist attractions. The calculations using the SAW method indicate that Sheikh Zayed Mosque has the highest preference value, making it the best tourist attraction according to this system. Testing shows that the system functions as expected, with consistent calculation results between manual and automated methods.